2010
DOI: 10.1063/1.3518300
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO:Al thin films onto different substrates

Abstract: In this paper we present some results regarding undoped and doped ZnO thin films deposited on various substrates like glass, silicon and kapton by rf magnetron sputtering. The influence of the amount of aluminum as well as the usage of different substrates on the final photovoltaic properties of the thin films is studied. For this, structuralmorphological and optical investigations on the thin films are conducted. It was found that three important factors must be taken into account for adjusting the final desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Thus, ZnO exhibits a wide bandgap for a semiconductor [8] and becomes more conductive [9] after doping with aluminum. However, the optimal value of Al doping may vary between 1 and 3%, as found in various studies [1,10,11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, ZnO exhibits a wide bandgap for a semiconductor [8] and becomes more conductive [9] after doping with aluminum. However, the optimal value of Al doping may vary between 1 and 3%, as found in various studies [1,10,11].…”
Section: Introductionmentioning
confidence: 96%
“…Extensive studies have shown that properties of the AZO thin films are highly dependent on the preparation technology, such as: RF magnetron sputtering [10], thermal oxidation [11,12], chemical vapor deposition [12], pulsed laser deposition [2,13,14], spray pyrolysis [15] and thermal deposition [16]. From these techniques, RF magnetron sputtering [10,17] is considered optimal in terms of high deposition rate, good control and the possibility of scaling to large areas (deposition on large substrates, e.g. 10 cm × 10 cm), high quality of deposition and without emission of toxic gases.…”
Section: Introductionmentioning
confidence: 99%